Global coordination of regulation and supervision in the financial sector (Economic and Political Thought, 2017)
The latest financial crisis revealed not only deficiencies of the marketeconomy systems but also of the regulatory and supervisory solutions thatshould at least lessen real consequences of wrong financial decisions. Normativearbitration that in the era of globalisation allows for the relocation ofa company registered office to a country with fewer legal requirements led tothe erosion of prudential standards. In order to counteract these tendencies,the biggest global economies established a coordination network closely linkingthe political aspect with the economic and financial one. The G-20 groupand the Financial Stability Board (FSB) are the most important elements ofthat coordination process. The article aims to analyse those groups’ mutualrelations. Remembering of course that original delegation for the G-20 groupis from sovereign states, the author believes that they can be interpretedin terms of a scheme: principal – agent, which is known in economic andpolitical sciences. On the other hand, the analysis of FSB activeness, withall the deficiencies resulting from incomplete subordination to the regimeof international public law, indicates that it plays the role of an institutionof macroprudential supervision over the global financial market. Thus, thedecrease in the intensity of the systemic risk, which may still become a reality,depends on its efficient functioning. The designed mechanisms of politicalpressure and efficient secondary delegation to specialised supervisory groupssensu stricto make the Financial Stability Board an efficient forum implementingthe tasks of macroprudential supervision.